Uncertainty of $L_{DEN}$ calculation for corona noise from Ultra High Voltage power lines using reference methods - Wszołek, Tadeusz (Archives of Acoustics, 2006)
Accordingly to the regulations contained in the European Noise Directive (END) and alsoin some legal acts being currently under legislative process in Poland, in the nearest future the$L_{DEN}$ and $L_{N}$ levels will be used as the basis for evaluation of corona noise from UHV powerlines. The paper presents an example of combined uncertainty evaluation for estimation oflong-term level ($L_{A, LT}$) and $L_{DEN}$ level for corona noise from UHV overhead power lines.Some specific features of that noise – large time variation of its level and spectral structure,dependent on the atmospheric conditions, and on the other hand often small distance from thebackground noise – are the reason that the evaluation of its estimation uncertainty is more difficultthen for some other, better “determined” noise sources. The partial uncertainties relatedto the measurement system and prediction method according to the reference methods for industrynoise were dealt with. The effect of the environment on the system and the measuredquantity have been distinguished and quantitatively determined.